Dietary replacement with food waste and black soldier fly larvae supplementation improved growth performance, nutrient digestibility and intestinal microbial population in broilers - Al-Qazzaz, Mohammed; Samsudin, Anjas Asmara; Idris, Lokman Hakim; Ismail, Dahlan; Akit, Henny (Friends Science, 2021)
This study was aimed to evaluate the effect of conventional ingredients replacement with alternative ingredients on growth performance, carcass quality, nutrient digestibility and intestinal microbial of broilers. One hundred twenty Cobb500 broiler chicks were randomly assigned to four diets. Corn, soybean meal and fish meal were replaced with rice waste, meat and bone waste and black soldier fly larvae (BSFL) at 0, 10, 30 and 50% to form four treatments. Body weight gain, feed conversion ratio and digestibility of crude protein and fat were improved in broilers fed the replacement diets. Feed intake was not affected by the treatments suggesting that the replacement diets were well accepted by the chicken. Escherichia coli was decreased in the cecum and Lactobacillus were increased in the intestines of broilers fed the replacement diets. The fiber and chitin contents in the replacement diets may alter intestinal bacterial fermentation leading to improved nutrient digestibility. However, abdominal fat percentage increased in broilers fed the replacement diets. In conclusion, conventional ingredients can be replaced with up to 50% rice waste, meat and bone waste and BSFL in the diets with promising effect on growth performance, nutrient digestibility and intestinal microbial populations.